2022
DOI: 10.31124/advance.19474733.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A (meta)governance framework for multi-level governance of inter-organizational project networks

Abstract: <p>Inter-organizational networks are frequently used to execute large and megaprojects. This study develops a theoretical framework for the governance of these networks. Twenty-eight case studies, each representing a network for a project, were assessed using 124 interviews in ten countries. A three-layer governance model is derived from the analysis. At the lowest layer (network governance) is the individual network of organizations collaborating in a project. This layer is explained through Multi-level… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…At the same time governance of networks facilitates the link between metagovernance and the governance of the network of horizontal and non-hierarchical organizations, representing a moderating relationship (Müller et al, 2022). Hence, we propose that: H2.2: The impact on Type II governance is moderated by Governance of Networks By proposing H2.1 and H2.2, we hypothesize that governance of networks acts as a mediator and as a moderator at the same time.…”
Section: H21: the Impact On Type I Governance Is Mediated By Governan...mentioning
confidence: 93%
See 4 more Smart Citations
“…At the same time governance of networks facilitates the link between metagovernance and the governance of the network of horizontal and non-hierarchical organizations, representing a moderating relationship (Müller et al, 2022). Hence, we propose that: H2.2: The impact on Type II governance is moderated by Governance of Networks By proposing H2.1 and H2.2, we hypothesize that governance of networks acts as a mediator and as a moderator at the same time.…”
Section: H21: the Impact On Type I Governance Is Mediated By Governan...mentioning
confidence: 93%
“…Network governance recognizes the governance of the joint execution of projects through the network. Adopting multi-level governance as the theoretical lens, Müller et al (2022) found that the hierarchical structure typically found at the top of hybrid formations of inter-organizational project networks can be explained through Type I governance with clear roles and responsibilities, distinct accountabilities and based on traditional governance theories (Davis, Schoorman, & Donaldson, 1997;Williamson, 1985). Additionally, they found that the more democratic interactions at the lower end of the hierarchy can be explained through Type II governance and being more situation dependent.…”
Section: Network Governancementioning
confidence: 99%
See 3 more Smart Citations